Portrait of the polemic of Fraud In Conventional and Sharia Insurance Company - Kristiana, Deranika Ratna; Hatta, Atika Jauharia (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p16, 2022)
This study examines the effect of fraud on insurance companies, both conventional and sharia insurance, from 2017 to 2021. This study aims to describe the existence of fraud committed through systems or humans, whether intentional or unintentional, even in Conventional and Sharia Insurance companies. The independent variables used are financial stability, financial targets, manager supervision ineffectiveness, auditor turnover, board turnover, and dualism positions. The insurance companies sampled in this study are listed on the Indonesia Stock Exchange and meet the criteria in this study. This study shows that financial stability affects fraud detection in financial statements. External pressure affects fraud detection, while the external pressure variable, ineffective supervision, auditor replacement, director change, and dualism position do not affect detecting fraudulent financial statements. Keywords: Fraud; Financial Stability; External Pressure; Ineffective Supervision; Change Of Auditor; Change Of Directors; Dualism Position.